PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN ATMOSFER WISATA MALAM KAMPUNG SUSUN KUNIR - Veronica, Selly; Aulia, Afina Nisa; Simanjuntak, Esra Revalina; Chandrawinata, Dita Bagus; Chandrawinata, Dito Bagus (Universitas Mataram, 2025)
Kampung Susun Kunir, located in the strategic corridor of Jakarta’s Kota Tua area, holds significant potential to be developed as a night tourism destination based on local culture. This community service program aimed to identify night tourism potentials and formulate its development concept through a participatory approach. The implementation took place from June 2024 to July 2025, involving local residents, all registered households, and the Kampung Kollektief team as supporting partners. The method included secondary data collection, field observation, focus group discussions, and information analysis to develop the concept based on four key elements of night tourism atmosphere: innovation, distinctive night scenery, attractions, and area identity. Findings indicate that the community’s warm social life, communal activities such as karaoke, traditional games, shared fruit salad (rujak) sessions, and the village’s night-time visual potential are the main strengths in building tourism appeal. The development strategy focuses on utilizing existing physical and socio-cultural potentials without replacing residents’ primary livelihoods, but instead adding economic value and strengthening social cohesion. This model is expected to serve as a reference for adaptive and sustainable community-based night tourism development in urban areas.